(3GdPgH GdEHQjR aj JaSjQ cJGH Gddg GdYRjRs - (3eMeO GdjOGdj Hf GdeNJGQ Hf eMeO SYjO GdOjeGfj,J (B1164 (3g` s
(3ChdgG (B:s
( (3hdGJJHYhG ef Ohfg ChdjGA (B) (3JWjYhfge ai eYUjJg JYGdi (B( (3bdjdkG eG JPcQhf (B) (3HGdJGA hGdjGA (B: (3JJYXhf s
(3BNQgG (B:s
( (3QHce CYde HeG ai fahSce (B) (3ef EVeGQ GdHQ hGdYbhb , hcCfg JgOjO s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JaSjQ (B150) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs